2005
DOI: 10.1590/s1413-70542005000200022
|View full text |Cite
|
Sign up to set email alerts
|

Composição bromatológica de silagens de sorgo (Sorghum bicolor (L.) Moench) aditivadas com forragem de leucena (Leucaena leucocephala (LAM.) DEWIT)

Abstract: O experimento foi realizado com o objetivo de avaliar os efeitos da adição de níveis crescentes de forragem de leucena na composição bromatológica da silagem de sorgo. O delineamento experimental usado foi o inteiramente casualizado, com cinco tratamentos e três repetições. O material ensilado consistiu de sorgo puro e sorgo com 10, 20, 30 e 40% de forragem verde de leucena. O sorgo forrageiro AG 2002 foi colhido aos 110 dias após o plantio e a leucena foi cortada no mesmo dia, colhendo-se ramos com diâmetro d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 3 publications
3
8
0
8
Order By: Relevance
“…Chemical and physical properties of sorghum silage showed that there was not difference in dry matter comparing pre and post-fermented sorghum. Values of dry matter in this work agree with Neumann et al (2004) who analyzed sorghum silage for beef cattle in the region of Rio Grande do Sul (Brazil), while differing from other researchers who obtained lower values (Evangelista et al, 2005;Rodriguez et al, 1999). The dry matter content is one of the main factors for well preserved silage because it is responsible to affect the type of fermentation and storage.…”
Section: Determination Of Aflatoxin Bsupporting
confidence: 68%
“…Chemical and physical properties of sorghum silage showed that there was not difference in dry matter comparing pre and post-fermented sorghum. Values of dry matter in this work agree with Neumann et al (2004) who analyzed sorghum silage for beef cattle in the region of Rio Grande do Sul (Brazil), while differing from other researchers who obtained lower values (Evangelista et al, 2005;Rodriguez et al, 1999). The dry matter content is one of the main factors for well preserved silage because it is responsible to affect the type of fermentation and storage.…”
Section: Determination Of Aflatoxin Bsupporting
confidence: 68%
“…Arundinaceum (Desv.) from Wet & J.R.Harlan were brought to be used as forage (Evangelista et al 2005;Rodrigues et al 2004;Vasconcelos et al 2012), Psorium guajava L. was brought for agricultural use (Siqueira et al 2012), others, such as Catharanthus roseus (L.) Don, Azadirachta indica A.Juss., Cynodon dactylon (L.) Pers., for use in landscaping (Christoffoleti and Aranda 2001;Menezes andHardoim 2013, Souza et al 2013a). There are still examples of species that were probably introduced accidentally, as Enneapogon cenchroides (Roem.…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed by Evangelista et al (2005) evidenced decreases in ADF content of sorghum silages when added 10, 20, 30 and 40% of Leucena.…”
Section: Stylosanthes Levels (%)mentioning
confidence: 96%